Normal Coronary Arteries: Our Experience at Ibrahim Cardiac Hospital & Research Institute - Chowdhury, Mashhud Zia; Khan, Saidur Rahman; Ali, Md. Liaquat; Karim, Md. Rezaul; Haq, M Maksumul (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 10-14 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13545